Maternal plasma n‐3 and n‐6 polyunsaturated fatty acid concentrations during pregnancy and subcutaneous fat mass in infancy. Issue 8 (29th June 2016) - Jelena Vidakovic, Aleksandra; Santos, Susana; Williams, Michelle A.; Duijts, Liesbeth; Hofman, Albert; Demmelmair, Hans; Koletzko, Berthold; Jaddoe, Vincent W.V.; Gaillard, Romy
Abstract : Objective: The associations of maternal plasma n‐3 and n‐6 polyunsaturated fatty acid (PUFA) concentrations during pregnancy with infant subcutaneous fat were examined. Methods: In a population‐based prospective cohort study among 904 mothers and their infants, maternal plasma n‐3 and n‐6 PUFA concentrations were measured at midpregnancy. Body mass index, total subcutaneous fat, and central‐to‐total subcutaneous fat ratio were calculated at 1.5, 6, and 24 months. Results: Maternal n‐3 PUFA levels were not consistently associated with infant body mass index or total subcutaneous fat. Higher maternal total n‐3 PUFA levels, and specifically eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid, were associated with higher central‐to‐total subcutaneous fat ratio at 1.5 months, whereas higher maternal total n‐3 PUFA levels were associated with lower central‐to‐total subcutaneous fat ratio at 6 months (all P values < 0.05). These associations were not present at 24 months. Maternal n‐6 PUFA levels were not consistently associated with infant subcutaneous fat. A higher n‐6/n‐3 ratio was associated with lower central‐to‐total subcutaneous fat ratio at 1.5 months only ( P value < 0.05). Conclusions: Maternal n‐3 PUFA levels during pregnancy may have transient effects on infant subcutaneous fat. Further studies are needed to assess the effects of maternal PUFA concentrations on fat mass development during early infancy.